Mechanism of Antiviral Action of Acetone on Rabbitpox Virus Replication - Chernos, V. I. (1972)
Acetone added to the maintenance medium in a 1% concentration reduces the yield of infectious rabbitpox virus in L-cell monolayer cultures by 90 to 97%. This concentration of the inhibitor is not toxic for cells. It was established that there is an inhibitor-sensitive stage late in the infectious cycle. Acetone exerted no significant influence on production of early viral messenger ribonucleic acid, formation of polyribosomes, deoxyribonucleic acid (DNA) replication, or protein synthesis. In the presence of acetone, the assembly of so-called “acetone particles” occurred. These particles are similar to normal virions by morphological and sedimentation properties but are slightly different from them in buoyant density. The amount of virus-specific DNA and the optical density of the “acetone particles” are the same as those of normal virions despite a 10- to 25-fold difference in the infectivity of the preparations.